As contribuições de Ernesto de Souza Campos para a ciência no Brasil: uma proposta metodológica aplicada a documentos históricos - Matos, Lígia Barini de (2015)
Preserving the memory of a population is of great importance because it determines the evolution of a people and traces its history perpetuates and strengthens their cultural identity. There are historic farms in the state that are rich in memory as Farm Santa Maria Monjolinho located on the outskirts of the city of São Carlos, which contains a large collection containing the history of the region and the country. It is estimated that there is in these documents have not unraveled much about the history of the development of science, health and education of our country. The aim of this research, raise with the first volume of the "Curriculum Vitae" - item that is part of historical documents belonging to Fazenda Santa Maria Monjolinho - contributions that Dr. Ernesto de Souza Campos brought to the areas of science and education for our country, and disseminate this knowledge along to the academic peers and also for society. Dr. Ernesto degree in civil engineering from the Polytechnic School in 1906 and medicine from the Faculty of Medicine and Surgery of São Paulo in 1918, Ernesto de Souza Campos brought major contributions to the development of the scientific and academic community of the country, as participation in the foundation of some universities, for example, the University of São Paulo. The aim of this research to trace its history and bring it to the attention of society, and other researchers, valuing the existing cultural heritage in the Santa Maria Monjolinho. For that were selected nine documents distributed over three phases of the life of Ernesto, as follows: Stage 1: life as an engineering student or engineer, 2nd phase: life as an engineer and a medical student, and Phase 3: life as an engineer and doctor. . These selected documents were analyzed between two sub-areas determined by their purpose being, institutionalization of science and knowledge generation, seeking contributions left by him from the civil engineering as well as medicine, and that reflect the production and institutionalization of science in Brazil.